Tariff structure and investment location: Peru in the 1990s - González-Vigil, Fernando (2001)
This article analyzes the effects of trade policy on the patterns of location of foreign direct investment (FDI) by country and sector. Particular attention is paid to FDI in manufactures, for which the market size is a very important locational factor, and therefore, so too is the preferential access to enlarged markets provided by trade agreements. Hence this article compares the performance of Peru in this field with those of its partners in the Andean Community of Nations (CAN), especially Colombia, which was the CAN's leading recipient of manufacturing FDI in the last decade. The analysis shows that Peruvian trade policy in the 1990s raised the cost of producing within the country, failed to give industrial activity levels of effective protection comparable to those prevailing in Peru's neighboring competitors, and made the country less attractive as a location for industrial firms interested in the Andean Community subregional markets. For those reasons, trade policy discouraged private investment in Peru, particularly FDI in manufactures with greater value added and technological level, diverted industrial investment to neighboring countries and facilitated an increase in imports of manufactures from those countries, thereby causing substantial harm to the industrialization and competitiveness of the Peruvian economy.